O brinquedo de miriti como prática pedagógico-cultural: representação e identidade - GONÇALVES, Isane da Conceição de Lima (2019)
The present work was carried out in the Popular Education Center Lighting the Lights (ECLAC), in the municipality of Abaetetuba; consisted of an ethnographic research that is characterized by the daily observation in the institution, through which I try to identify if the language of Toy Miriti is used as pedagogical-cultural practice to highlight the local culture. For the production of data I made use of observation and conversations, described in the field diary, in order to explain the situations related to Miriti Toy, besides observations, I captured images; I conversed informally with the research subjects. From this, I tried to answer the following questions: How is the miriti toy used in the classroom as a pedagogical-cultural practice? How does the representation of the toy of miriti constitute the identity of the students? The research objectives are: Describe how miriti toy is used in the classroom as pedagogical-cultural practice; Reflect the representations of the toy of miriti and how these constitute the identities of the students. Silva (2004), which deals with the influence of the curriculum on the constitution of identities, also brings Silva (2000), who addresses the question of identities as a cultural and social construction. In order to address the importance of culture as a pedagogical force in the curriculum, I used Ribeiro, Lobato and Alexandre (2017) and, finally, Jones Gomes (2013), who talks about the toy of miriti approaching tradition and explaining how it is present in the municipality of Abaetetuba. As results I realized that the elements of the local culture are still little inserted in the curriculum, that privileges the knowledge of the erudite culture; however, the insertion of this knowledge in the classroom is extremely important for the appropriation of traditional knowledge, for the knowledge of the elements and artifacts of our culture, and for the constitution of identities.